Genistein Effects on Various Human Disorders Mediated via Nrf2 Signaling - Shirvanian, Kasra; Vali, Reyhaneh; Farkhondeh, Tahereh; Abderam, Amir; Aschner, Michael; Samarghandian, Saeed (Current Molecular Medicine, 2024)
Genistein is a flavonoid, mostly found in soybean extract and is widely used for its antioxidant and anti-inflammatory activities. Genistein can interact with estrogen receptors due to its structural similarities to estrogen. It also inhibits protein tyrosine kinases and affects a variety of intracellular signal transductions. Genistein attenuates oxidative stress via diverse cellular mechanisms. However, nuclear factor (erythroidderived 2)-like 2 (Nrf2), the main antioxidant regulator, potentiates genistein's antioxidant effects and reduces cell damage. Nrf2 includes of seven domains and controls the expression of the phase II antioxidant enzymes to decrease oxidative stress. In this review, we address findings related to Nrf2 signaling pathways in the context of genistein's effects on diverse human diseases.
Keywords: nuclear factor erythroid 2-related factor 2